Анна Каренина: роман в 8 ч. (Л. Н. Толстой) - Толстой Лев Николаевич (1984)
Экземпляры: ф.2 (1984) / Инвентарный номер: 7811 / Цена: 2.40 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Т 53 / ББК: 84(2Рос=Рус)1